Pengaruh Konten Marketing Akun Tiktok @EYEBOST.ID Terhadap peningkatan Brand Awarness Eyebost - Nurhidayat, Imam Syarifudin; Annisa, Fhena (Komunika : Jurnal Ilmiah Komunikasi, 2025)
The rapid growth of social media has transformed how brands interact with their audiences. TikTok has emerged as one of the most effective platforms for implementing creative and interactive content marketing strategies. This study focuses on the official TikTok account @eyebost.id, owned by the Eyebost brand, which utilizes educational and promotional content to build brand awareness. A quantitative approach was employed using a survey of 398 respondents, analyzed through simple linear regression with SPSS. The results indicate a positive and significant influence between content marketing and brand awareness, with an R² value of 0.623. This finding suggests that engaging and consistent content strategies can increase brand awareness by up to 62.3%. The study highlights the strategic role of TikTok in strengthening brand positioning and provides practical insights for developing effective digital marketing communication strategies in the social media era.